Peculiarities of planning the ecological-recreational framework of land use system in Lviv region - Zanchuk, O. (Land Management, Cadastre and Land Monitoring, 2024)
It has been elucidated that the ecological framework of the land use system comprises a set of core components with varying levels and arranged according to the principle of "from general to specific," as well as components connected by ecological corridors of the ecological network. In Lviv region, the ecological framework of the land use system serves as the foundational basis for the ecological-recreational framework. With the increasing anthropogenic activity and the growing impact of recreational activities, encompassing all forms of leisure, including tourism and other activities, it’s essential to develop infrastructure that supports these activities. One way to achieve this is by creating a land use system model that combines the functions of nature conservation and recreational systems. In this case, the ecological and ecological-recreational frameworks of the land use system should be integrated. The ecological-recreational framework refers to a territory comprising natural and recreational resources connected by ecological links. Its primary objective is to protect and conserve territories while promoting rational recreational land use. This framework involves not just natural areas but also tourist-attracting territories with current infrastructure, such as ecological-recreational clusters. These clusters aim to foster economic development, attract investments, enhance the efficiency of current recreational areas, and introduce new recreational activities in the region. An analysis conducted in 2023 of the land use in the ecological network of Lviv region revealed that only 26.4% of the region’s land has been developed. This includes the use of key territories (natural cores) at 51.4%, while connecting territories (ecological corridors), buffer territories, and restoration territories have not been developed at all. Based on this ecological framework data, the land use for recreational purposes in the region has been determined. It was concluded that only 53.4% of the projected area is currently in use, with 50% allocated for recreational and health purposes. Urban zoning in Lviv region has identified the following main types of land use: 1) urbanization type, which includes mixed land use for residential and commercial-public buildings, agriculture, nature conservation, and recreation, with centers in Lviv, Chervonohrad, Drohobych, and Stryi; 2) agricultural land use type; 3) recreational and health resort land use type; 4) land use for industrial parks in border territories; 5) land use for transportation, including international transport corridors. It has been observed that over a period of 12 years, there has not been any significant redistribution of land use by the main types. The agricultural land use type decreased by only 0.3% instead of the forecasted 1.5%. The area of residential and public buildings increased by only 0.1% instead of the projected 0.4%, and other construction increased by 0.6%. The area of transportation, communication, and technical infrastructure land use decreased by 0.5%. Negative changes have been observed in the transformation of natural reserve land use, which increased by 1.8% instead of the expected twofold increase from 6.1% to 10.8%. A forecasted structure of land use development by its main types has been developed across the districts of the region, with a focus on the development of recreational and health resort land use up to 2035. Keywords: ecological-recreational framework of land use system, ecological network, land zoning by land use types.